Amaranthus rajasekharii (Amaranthaceae), a new species from Kerala (SW-India) - Sindhu, Arya; Venugopalan Nair Saradhamma, Anilkumar; Kalarikkal, Vishnu Walsan; Iamonico, Duilio (Phytotaxa, 2020)
A new species of Amaranthus from Kerala (SW-India)—Amaranthus rajasekharii—is described and illustrated. Macro- and micro-morphological descriptions (with SEM analysis of pollen and seed), as well as original photos and drawings were provided. The new species is similar to A. dubius, from which it differs by stem color, inflorescence structure, gynoecium colour, number of stamens, and shape and lenght of tepals and bracts in pistillate flowers, seed ornamentation, and pollen architecture.